Endurance Training for Cardiovascular Health: Insights into Risk Reduction and Heart Disease Prevention - Charzewski, Piotr; Starzyk, Agnieszka (Quality in Sport, 2025)
Endurance training significantly benefits from strong cardiovascular health, as it relies on the efficient delivery of oxygen and nutrients to working muscles. A robust cardiovascular system enhances key factors such as cardiac output, stroke volume, and capillary density, which optimize oxygen transport and utilization during prolonged physical activity. This improved vascular efficiency reduces strain on the heart, allowing athletes to sustain higher intensities for longer durations. Endurance training also improves aerobic capacity (VO₂max) and accelerates recovery rates, enabling individuals to handle greater training loads and recover more effectively. Together, these adaptations create a positive feedback loop where endurance training strengthens cardiovascular health, further enhancing performance and resilience.